Competing on Internet time lessons from Netscape and its battle with Microsoft - Cusumano, Michael A. 1954-; Yoffie, David B. (New York, NY The Free Press, a division of Simon & Schuster Inc., 1998)
In this analysis of strategy-making and product innovation in the dynamic markets of commercial cyberspace, Michael Cusumano and David Yoffie draw vital lessons from Netscape, the first pure Internet company, and show how it employs the techniques of "judo strategy" in its pitched battle with Microsoft, the world's largest software producer. With a new afterword updating the events of the year following publication of the hardcover edition, Competing on Internet time is instructive reading for all managers, engineers, and entrepreneurs who want to succeed in ultra-fast-paced markets.
Competing in the age of the Internet -- Creating the company: the vision, the people, and the organization -- Competitive strategy: using judo to turn on opponent's strength into weakness -- Design strategy: leverage through cross-platform techniques -- Development strategy: flexible, fast, and "slightly out of control" -- Competing on Internet time: lessons from Netscape and Microsoft -- Appendixes : 1. Netscape's chronology ; 2. Netscape's products.
Includes bibliographical references (pages 343-351) and index.
Keywords: Netscape Communications Corporation; Microsoft Corporation; Internet software industry -- United States; Competition -- United States